Characteristics of compression wave propagation and energy absorption effects in dry sandy soil - Peng Cui; Tian Su; Le Liu; Teng Wang; Bangxiang Li; Xuetao Guan; Xuefeng Mei (Scientific Reports)
Abstract The mechanical responses of sandy soil under dynamic loading is closely related to protective engineering and geotechnical engineering, is still not fully understood. To investigate the energy attenuation law and propagation velocity of compressed waves in dry sandy soil, this paper focuses on the dynamic response of compression waves in the specimen under single impact and repetitive impact conditions using an improved split Hopkinson pressure bar (SHPB). The results reveal that the length of the specimen follows an exponential relationship with the attenuation of the peak stress. As the length of the specimen increases from 40 to 240 mm, the attenuation rate of the peak stress increases from 26.3 to 99.0%. The velocity of the peak stress decreases with increasing specimen length, indicating a correlation between these two factors. Furthermore, the impact test results reveal that the number of impacts and the density of the specimen affect the attenuation of the compressed wave. As the number of impacts increases, the density of the specimen also increases, resulting in a gradual decrease in the degree of compressed wave attenuation. When the density increases from 1.60 to 2.29 g/cm3, the attenuation of the compressed wave decreases by 17.0%, and the energy absorption density increases from 0.241 to 1.172 MJ/m3, representing a 386.3% increase. Additionally, the study reveals that the energy absorption efficiency decreases with increasing number of impacts at the same stress level. However, after two impacts, the energy absorption efficiency approaches a steady state. At the same strain level, the energy absorption efficiency remains consistent, indicating the material’s energy absorption characteristics.